2022
DOI: 10.3390/ani12202823
|View full text |Cite
|
Sign up to set email alerts
|

Oviduct Transcriptomic Reveals the Regulation of mRNAs and lncRNAs Related to Goat Prolificacy in the Luteal Phase

Abstract: The oviduct is associated with embryo development and transportation and regulates the pregnancy success of mammals. Previous studies have indicated a molecular mechanism of lncRNAs in gene regulation and reproduction. However, little is known about the function of lncRNAs in the oviduct in modulating goat kidding numbers. Therefore, we combined RNA sequencing (RNA-seq) to map the expression profiles of the oviduct at the luteal phase from high- and low-fecundity goats. The results showed that 2023 differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Previous work has started uncovering the amounts of protein and mRNA expression in the same sample to better understand probable molecular mechanisms and identify reliable biomarkers of specific biological processes [ 24 , 74 ]. In this study, we utilized transcriptomic data generated in the oviduct from the same tissue sample, which we previously published [ 75 , 76 ], to complement the proteomic analysis. Comparing the two phases, our transcriptomics and proteomics results showed that many more transcripts can be identified than proteins in the oviduct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has started uncovering the amounts of protein and mRNA expression in the same sample to better understand probable molecular mechanisms and identify reliable biomarkers of specific biological processes [ 24 , 74 ]. In this study, we utilized transcriptomic data generated in the oviduct from the same tissue sample, which we previously published [ 75 , 76 ], to complement the proteomic analysis. Comparing the two phases, our transcriptomics and proteomics results showed that many more transcripts can be identified than proteins in the oviduct.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput RNA sequencing (RNA-seq) was conducted following our previously published studies [ 75 , 76 ] and using the same oviduct samples as in protein extraction. Briefly, total RNAs from the 20 oviduct tissues in follicular and luteal phases were extracted by TRIzol reagent (Invitrogen, Carlsbad, CA, USA), respectively.…”
Section: Methodsmentioning
confidence: 99%